Epidemiology of thymomas and thymic carcinomas in the United States and Germany, 1999-2019 - Gerber, Tiemo Sven; Strobl, Stephanie; Marx, Alexander; Roth, Wilfried; Porubsky, Stefan (Frontiers in Oncology, 2024)
Introduction Mediastinal tumors, particularly non-neuroendocrine thymic epithelial tumors (TET) are relatively uncommon, posing challenges for extensive epidemiological studies. This study presents a comprehensive analysis of these tumors in the United States (US) and Germany (GER) from 1999 to 2019. Methods Patients aged 0-19 (n=478) and ≥20 years (n=17,459) diagnosed with malignant tumors of the anterior mediastinum were identified from the Surveillance, Epidemiology, and End Results registry (SEER) and the Zentrum für Krebsregisterdaten (ZfKD) databases. Results Among patients aged ≥20 years, TETs accounted for the most prevalent anterior mediastinal tumors (US/GER: 63%/64%), followed by lymphomas (14%/8%). For patients <20 years, predominant tumors included germ cell tumors (42%/14%), lymphomas (38%/53%), and TETs (10%/27%). The overall annual incidence of thymoma was 2.2/2.64 (US/GER) per million inhabitants and for thymic carcinomas 0.48/0.42. The male-to-female ratio was 1:1.09/1.03, and the mean age 59.48 ± 14.89/61.33 ± 13.94. Individuals with thymomas, but not thymic carcinomas, exhibited a 21%/29% significantly heightened risk of developing secondary malignancies compared to controls with non-thymic primary tumors. Discussion This study provides a comparative analysis of anterior mediastinal tumors, particularly TETs, in the US and GER over the past two decades. Furthermore, it highlights a significantly elevated incidence of secondary malignancies in thymoma patients.